Neurotransmitters and Electrophysiological Changes Might Work as Biomarkers for Diagnosing Affective Disorders. (20th September 2021) - Liang, Fei; Feng, Rou; Gu, Simeng; Jiang, Shan; Zhang, Xia; Li, Naling; Xu, Minghong; Tang, Yiyuan; Wang, Fushun
Abstract : Affective disorders are the leading causes of human disability worldwide; however, the diagnosis is still hard to define, because emotion is the least study subjects in psychology. Recent emotional studies suggest that human emotions are developed from basic emotions, which are evolved for fundamental human lives. Even though most psychologists agree upon the idea that there are some basic emotions, there is little agreement on how many emotions are basic, which emotions are basic, and why they are basic . In our previous papers, we suggested that there are three basic emotions: joy, fear, and disgust. These basic emotions depend on the peptides and monoamines: dopamine-joy (peptides-reward), norepinephrine-fear (anger), and serotonin-disgust (sadness) . Further tests with event-related potentials (ERP) found that joy, fear, and disgust showed the fastest response compared with other emotions, suggesting that they are fast automatic responses, which confirmed that these three emotions are prototypical emotions. Other basic emotions, anger and sadness, are due to object induced behaviors instead of sensation of object, so they developed secondary to prototypical emotions. Thus, we concluded that only joy, fear, and disgust are prototypical emotions, which can mix into other emotions, like the primary colors. In all, the neural substrates for all emotions, including the affections, are possibly monoamine neuromodulators: joy-dopamine (peptides), fear (anger)–norepinephrine, and disgust-serotonin. We hope these basic emotional studies will offer some neural mechanisms for emotional processing and shed lights on the diagnosis of affective disorders.